ANALYSIS OF WORK ACCIDENT RISK FACTORS USING JOB SAFETY ANALYSIS (JSA) AND FAILURE MODE AND EFFECT ANALYSIS (FMEA) METHODS (A CASE STUDY OF DYEING-FINISHING IN THE TEXTILE INDUSTRY X) - Sarah Fadhlillah Sahida, Raden
As the industry grows, the dangers of occupational risks increase significantly. One of the most important parts of an industry is human resources, which experience various kinds of risks. This research aims to identify and analyze various hazards in the textile industry using Job Safety Analysis and Failure Mode and Effect Analysis (FMEA). The process of identifying hazards and risks is obtained through interviews and field observations. This research uses a cross-sectional study conducted at the Dyeing-Finishing Department. The Risk Priority Number (RPN) in FMEA is determined based on severity, occurrence, and detection levels. Then PRN is categorized into low risk (RPN ? 50), moderate risk (RPN = 51-100), high risk (RPN ? 101-200), and very severe (RPN ? 201). A total of 49 risks were found in 8 machine units in the Dyeing-Finishing Department. 17% were found to be at a very severe level, 57% at a high level, 20% at a moderate level, and 6% at a low level. The scouring process and jet dyeing process have the most risks compared to other processes. Hands caught in the jet dyeing process have the highest RPN, namely 269, and poisoning in the scouring process has the lowest RPN, namely 35.68. This research revealed that more than 64% of the risks detected were unacceptable risks indicating dangerous conditions for workers in the textile industry. The risk of hands getting caught and being crushed by the roll is the most dangerous risk in this Department. Implementation of safety measures such as training programs, engineering controls, and provision of personal protective equipment (PPE) is recommended. The selection of alternative solutions provided to reduce the level of risk that exists in the Dyeing-Finishing Department and to obtain a more feasible solution cannot be separated from the cost budget calculation. This is to provide recommendations and calculate the benefits of providing recommendations using the Benefit-Cost Analysis method so that it will be easier for the company to determine the alternatives most needed in the company. Based on the results of analytical calculations, alternative solutions and values from BCA were obtained for each process in the Dyeing-Finishing Department. The BCA value for the fur burning process is providing impact safety gloves B/C 12.29, providing a dust mask B/C 5.36, providing anti-flame gloves B/C 2.86. The BCA value in the scouring process is providing impact safety gloves B/C 12.29, providing goggles B/C 8.82, providing safety boots B/C 2.99. The BCA value in the Jet Dyeing process is providing goggles B/C 8.66, providing impact safety gloves B/C 6.14, and completing lighting in the stair area 4.18. The BCA value in the cold pad batch process is providing goggles B/C 11.76, providing lighting in the stair area B/C 4.18, providing safety boots B/C 3.48. BCA's value in the washing process is providing goggles B/C 11.76, providing safety boots B/C 3.48, providing training to workers B/C 2.86. The BCA value for the thermosol process is providing goggles B/C 11.76, providing impact safety gloves B/C 8.19, providing training to workers B/C 3.07. BCA's value in the stenter process is providing impact safety gloves B/C 8.19, providing training to workers B/C 3.07, and installing sensor equipment 2.51. The BCA value in the drying process is providing safety boots B/C 10.46, providing safety helmets B/C 10.46, providing impact safety gloves B/C 8.19. Where for all comparison results between the cost value of accident costs and the benefits of alternative control costs, show that the B/C Ratio is > 1 or the project with all control alternatives is feasible.